Periodismo digital y su impacto en los medios de comunicación tradicional del cantón Quevedo, año 2021 - Cordones Sevillano, Elias David (2022)
This degree work presents digital journalism and its impact on the traditional media of the Quevedo canton, adding its progress over time and where the benefits of using digital media as a new modality to communicate and interact are highlighted, since Currently, information has become global thanks to the internet. The methodology that was applied in the research work was the quantitative and qualitative approaches in order to more conveniently detail the problem that exists, and to be able to propose real solutions. Field research was used to acquire information in an insightful and timely manner from the different communication media of the Quevedo Canton. The deductive and inductive method was awarded to establish digital journalism and its impact on the traditional media of the Quevedo canton. The types of techniques such as field observation and surveys, adding a form as an instrument, which was used in order to learn more about the variables raised, and thus collect information with greater accuracy and fidelity, thus evidencing surprising results. Within the research project, a small sector of 100 citizens was established as a field population, of which 80 citizens were determined by calculating the sample. The acceptance of the recommendations and proposals was finalized favorably, in addition, a correct application of digital journalism was determined within the traditional media of the Quevedo canton.